2014
DOI: 10.7314/apjcp.2014.15.2.957
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Associations between Vitamin D Metabolism-Related Gene Variants and Risk of Colorectal Cancer

Abstract: In this study, no significant difference was observed for VDR (rs2238136), GC (rs4588), CYP2R1 (rs12794714), and CYP27B1 (rs3782130) gene variants in either genotype or allele frequencies between the cases with CRC and the controls and this lack of difference remained even after adjustment for age, BMI, sex, smoking status, NSAID use, and family history of CRC. Furthermore, no evidence for effect modification of the variants and CRC by BMI, sex, or tumor site was observed. Conclusions: Our findings do not supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…However, other studies have found more inconsistent results (Poynter et al, 2010;Mahmoudi et al, 2014). Inverse relationship between serum vitamin D level and colorectal cancer risk has been demonstrated by a recent study .…”
Section: Discussionmentioning
confidence: 92%
“…However, other studies have found more inconsistent results (Poynter et al, 2010;Mahmoudi et al, 2014). Inverse relationship between serum vitamin D level and colorectal cancer risk has been demonstrated by a recent study .…”
Section: Discussionmentioning
confidence: 92%
“…Three studies showed no associations between SNPs in these genes and overall risk for colorectal cancer (27, 29, 30), while another report demonstrated a nominal relationship between the CYP24A1 polymorphism rs4809958 and risk for colon cancer (28). In the present study, no association between rs4809958 and overall adenoma recurrence, nor any adenoma characteristic, was observed, which is consistent with the majority of the published literature for colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results were not consistent with several meta-analysis about VDR BsmI polymorphism and other cancer risk. For instance, Mahmoudi et al (2014) recently found that Vitamin D Metabolism -Related Gene (including VDR) Variants was not associated with Risk of Colorectal Cancer in Iranian population. In recent, Zhang et al (2013) performed a meta-analysis to detect VDR BsmI polymorphism and ovarian cancer risk and found that there was no association between VDR BsmI polymorphism and susceptibility to ovarian cancer in Caucasians.…”
Section: Discussionmentioning
confidence: 99%